2016
DOI: 10.1534/g3.116.028902
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the Barley Chromosome 6H Net Form Net Blotch Susceptibility Locus

Abstract: Net form net blotch, caused by the necrotrophic fungal pathogen Pyrenophora teres f. teres, is a destructive foliar disease of barley with the potential to cause significant yield loss in major production regions throughout the world. The complexity of the host–parasite genetic interactions in this pathosystem hinders the deployment of effective resistance in barley cultivars, warranting a deeper understanding of the interactions. Here, we report on the high-resolution mapping of the dominant susceptibility lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 46 publications
0
58
0
Order By: Relevance
“…It was reported that sensitivity to a proteinaceous necrotrophic effector, produced by Ptt and mapped to barley chromosome 6H, was responsible for 31% of the variation observed in disease (Liu et al, 2015). These findings collectively emphasize the complexity of the host-parasite genetic interactions in this pathosystem and suggest that barley breeding programs should also consider eliminating dominant susceptibility genes or genes inducing necrotrophic effector-triggered susceptibility to develop Ptt-resistant cultivars (Liu et al, 2015;Richards et al, 2016). It is possible that differential production of this necrotrophic effector contributes to the virulence of different isolates of Ptt.…”
Section: ------------------------------------------------------------mentioning
confidence: 86%
See 4 more Smart Citations
“…It was reported that sensitivity to a proteinaceous necrotrophic effector, produced by Ptt and mapped to barley chromosome 6H, was responsible for 31% of the variation observed in disease (Liu et al, 2015). These findings collectively emphasize the complexity of the host-parasite genetic interactions in this pathosystem and suggest that barley breeding programs should also consider eliminating dominant susceptibility genes or genes inducing necrotrophic effector-triggered susceptibility to develop Ptt-resistant cultivars (Liu et al, 2015;Richards et al, 2016). It is possible that differential production of this necrotrophic effector contributes to the virulence of different isolates of Ptt.…”
Section: ------------------------------------------------------------mentioning
confidence: 86%
“…The seven Ptt and Ptm isolates examined represented six and five different pathotype groups, respectively, including the predominant pathotype groups C4 and E9 for Ptt and V1 and T1 for Ptm (Table 1). Moreover, the pathogen and host genotype interaction in this pathosystem is very complex and still not well understood (Liu et al, 2015;Richards et al, 2016). No clear pattern was observed in a recent study with respect to the geographic distribution of Ptt and Ptm pathotypes across the Canadian prairies (Akhavan et al, 2016a).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations